PENGARUH TINGKAT LITERASI KEUANGAN PEMILIK USAHA TERHADAP PENGELOLAAN KEUANGAN. STUDI KASUS: UMKM DEPOK - Birawani D. Anggraeni (Program Pendidikan Vokasi Universitas Indonesia, 2015)
Abstract. Financial literacy affects a person's way of thinking on the financial condition and influencestrategic decisions in terms of finances and better management for business owners. This study usessecondary data as study materials which will be given to the micro level that businesses with aturnover of up to 300M per year in which the segment in general do not have good financial recordsto then be used as financial statements. In a study using 12 samples of SMEs in the area of Depokrandomly selected. This study uses processed using descriptive statistics as well as the weighting atthe level of financial literacy.Results from this study indicate that the level of financial literacy of low business owners sothat the effect on the ability to manage finances. This is reflected in the financial results of theattitude of business owners where they merely record the receipt and expenditure of financialbusiness without being accompanied by supporting documents storage. Business owners so far havenot made the budget as a basis for evaluating the performance of their businesses. In addition theability of business owners to manage cash surplus and deficit shows the majority of using banks ornon-banks. They have not yet reached the stage of investing in financial products. Simple research isexpected to contribute to the field of accounting related to business continuity, especially in terms offinancial management business through increased financial literacy.Keywords:. financial literacy, financial management, record keeping, budget